Perancangan Aplikasi Masdika Untuk Pembelajaran Bahasa Jawa Krama - Irawan, Dimas; Dewi, Putri Novika (Universitas Dinamika, 2025)
Joseph Errington conducted a study concluded that the use of the Javanese language since 1998 is starting to fade. The influencing factoris the rare usage of the language within the scope of family, school or work. Though the Governor of Central Java in 2014 established a regulation requiring officers of the Central Java Provincial Government to use the Javanese language every Thursday, the regulation did not work well since the Javanese language has a level of speech that is not easy to do first on the variety of manners. Therefore, it is necessary to design a mobile application that can assist in communicating using the Javanese Krama language. This design approach uses qualitative methods, interview data, observation, documentation, and literature studies. The data analysis method used the 5W + 1H then media development used the MDLC (Multimedia Development Life Cycle) method. The results of the analysis show that the mobile application media is the right medium for the target audience aged 20 to 35 years, and is expected to be able to 'teach' and 'get used to' the use of Krama Javanese.